Design and Construction of a Pure Sine Wave Inverter (Journal of Informatics and Mathematical Sciences, 2017)
This research is a design and implementation of a sine wave inverter circuit developed to run AC appliances at a low cost which high efficiency. The design consists of two stages i.e. the DC-DC step up stage and a DC-AC Inverter stage. The DC-DC step up converter is based on a push-pull design to step 24VDC to 300VDC. Pulse width modulation was used i.e. the SG3525 pulse width Modulator. The DC-AC inverter stage comprised of four power mosfets in an H-bridge configuration, driven by a 40 kHz square wave encoded/modulated by a 50Hz sine wave that was derived from a TL084 quad op amp sine wave oscillator. An output voltage range of about 240-260VAC from 300VDC input was obtained. A low pass filter was used to filter out the high frequencies and thus isolate the harmonics so a 50 Hz fundamental frequency was retained.
Keywords: Inverter; Sine wave; Oscillator; Transformer